Rewiring of the Endocrine Network in Triple-Negative Breast Cancer - Li, Kaixuan; Zong, Dongjiang; Sun, Jianrong; Chen, Danxiang; Ma, Minkai; Jia, Liqun (Frontiers in Oncology, 2022)
The immunohistochemical definition of estrogen/progesterone receptors dictates endocrine feasibility in the treatment course of breast cancer. Characterized by the deficiency of estrogen receptor α, ERα-negative breast cancers are dissociated from any endocrine regimens in the routine clinical setting, triple-negative breast cancer in particular. However, the stereotype was challenged by triple-negative breast cancers’ retained sensitivity and vulnerability to endocrine agents. The interplay of hormone action and the carcinogenic signaling program previously underscored was gradually recognized along with the increasing investigation. In parallel, the overlooked endocrine-responsiveness in ERα-negative breast cancers attracted attention and supplied fresh insight into the therapeutic strategy in an ERα-independent manner. This review elaborates on the genomic and non-genomic steroid hormone actions and endocrine-related signals in triple-negative breast cancers attached to the hormone insensitivity label. We also shed light on the non-canonical mechanism detected in common hormone agents to showcase their pleiotropic effects.